Seasonality in spatial distribution: Climate and land use have contrasting effects on the species richness of breeding and wintering birds. Issue 13 (20th June 2019) - Kawamura, Kazuhiro; Yamaura, Yuichi; Senzaki, Masayuki; Ueta, Mutsuyuki; Nakamura, Futoshi
Abstract: Aim: Many studies have examined large‐scale distributions of various taxa and their drivers, emphasizing the importance of climate, topography, and land use. Most studies have dealt with distributions over a single season or annually without considering seasonality. However, animal distributions and their drivers can differ among seasons because many animals migrate to suitable climates and areas with abundant prey resources. We aim to clarify seasonality in bird distributions and their drivers. Location: Japan. Methods: We examined the effects of climate (annual mean temperature, snow depth), topography (elevation), and land use (extent of surrounding habitat) on bird species richness, in the breeding and wintering seasons separately, using nationwide data (254 forest and 43 grassland sites, respectively). We separately analyzed the species richness of all species, residents, short‐, and long‐distance migrants in forests and grasslands. Results: In the breeding season, the annual mean temperature negatively affected all groups (except for forest and grassland residents), and the extent of surrounding habitat positively affected many groups. By contrast, in the wintering season, temperature positively affected all groups (except for forest residents), and the extent of surrounding habitat positively affected only grassland long‐distance migrants. In both seasons, the species richness of forest and grassland residents was high in regions of moderate and high temperature, respectively. Moreover, snow depth negatively affected all forest groups in the wintering season. Mapping expected species richness suggested that regions with different climates served as habitats for different groups during different seasons. Main conclusions: All regions were important bird habitats depending on the season, reflecting the contrasting effects of temperature across seasons. In the breeding season, surrounding land use was also an important driver. To understand the seasonal role that each region and environment plays in maintaining species/communities, a large‐scale study considering both environmental seasonality and species distribution is needed. Abstract : Many studies have examined large‐scale distributions of various taxa and their drivers, emphasizing the importance of climate, topography, and land use. Most studies have dealt with distributions over single seasons or annually without considering seasonality. We showed that all regions of Japan were important bird habitats depending on the season, reflecting the contrasting effects of temperature across seasons.